2015
DOI: 10.1007/978-3-319-17641-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Ventricular Fibrillation and Defibrillation: The Virtual Electrode Hypothesis

Abstract: Ventricular fibrillation is the major underlying cause of sudden cardiac death. Understanding the complex activation patterns that give rise to ventricular fibrillation requires high resolution mapping of localized activation. The use of multi-electrode mapping unraveled re-entrant activation patterns that underlie ventricular fibrillation. However, optical mapping contributed critically to understanding the mechanism of defibrillation, where multi-electrode recordings could not measure activation patterns dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Therefore, the electrical energy can propagate into tissue deeper than the superficial layers when the shock energy follows the cell bundles in accordance with the sawtooth mechanism. On the basis of the sawtooth model, if an electric field is sufficiently strong, the transmembrane potential in the depolarized areas of all cells reaches the activation threshold and initiates local excitation, which spreads to the hyperpolarized areas, and the entire cell chain is activated almost simultaneously [12]. In this study, the temporal sawtooth pattern was observed at the tissue level during high-frequency defibrillation.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the electrical energy can propagate into tissue deeper than the superficial layers when the shock energy follows the cell bundles in accordance with the sawtooth mechanism. On the basis of the sawtooth model, if an electric field is sufficiently strong, the transmembrane potential in the depolarized areas of all cells reaches the activation threshold and initiates local excitation, which spreads to the hyperpolarized areas, and the entire cell chain is activated almost simultaneously [12]. In this study, the temporal sawtooth pattern was observed at the tissue level during high-frequency defibrillation.…”
Section: Introductionmentioning
confidence: 67%
“…In optical mapping experiments under real cathode stimulation, the cardiac tissue near the electrodes depolarizes, which generates two virtual anodes and causes lateral myocardium hyperpolarization. This phenomenon explains how remote tissue not directly under the shocking electrodes can have transmembrane potential responses from the shock [12,16,17]. The virtual electrode hypothesis is more applicable to biphasic shocks than to monophasic shocks possibly because of the immediate phase reversal of tissue responses during the shock [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated cardiomyocytes are still an important model to study defibrillation because stimulation can be used as a proxy for defibrillation. Stimulation is a viable proxy on theoretical grounds, because the success of defibrillation depends on whether a shock activates enough of the cardiac tissue 15,16,31 (but our data hereunder suggest that it has limitations). Stimulation of individual myocytes with nanosecond pulses is possible, 32,33 and the mechanism of stimulation likely involves electroporation of the plasma membrane.…”
Section: Introductionmentioning
confidence: 91%
“…Reentry refers to a circus movement of advancing wave front of depolarization through a circuit within the heart muscle which usually involves a critical barrier around which the wave front advances (Mines, 1913;Wit , 1978). This barrier could be a fixed anatomic barrier such as a scar, area of ischemia, or an anatomic structure such as a valve, or it can be virtual and even be mobile (Boukens et al, 2015). In several types of arrhythmias, the circuit is large and macroscopic involving much of the heart.…”
Section: Electrophysiology Of Vfmentioning
confidence: 99%